Strategic human resource management - Tang, Guiyao; Wei, Li-Qun (World Scientific, 2024)
Strategic human resource management (SHRM), as a crucial foundation for the survival and development of a firm, linking human resource management with a firm's strategic objectives to achieve sustainable competitive advantage. Numerous studies and practices have proven that the implementation of SHRM is conducive to acquiring core competitiveness and boosting competitive advantage. In response to the changes that are taking place in HRM practices, it is absolutely necessary for students and managers to learn SHRM systematically.